2023
DOI: 10.1101/2023.05.29.542712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering deep-sea chemosynthetic symbiosis by single-nucleus RNA-sequencing

Abstract: Bathymodioline mussels dominate deep-sea methane seep and hydrothermal vent habitats and obtain nutrients and energy primarily through chemosynthetic endosymbiotic bacteria in the bacteriocytes of their gill. However, the molecular mechanisms that orchestrate mussel host-symbiont interactions remain unclear. Here, we constructed a comprehensive cell atlas of the gill in the mussel Gigantidas platifrons from the South China Sea methane seeps (1100m depth) using single-nucleus RNA sequencing (snRNA-seq) and whol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 110 publications
0
0
0
Order By: Relevance
“…3P ). In a previous study ( 45 ), a similar cell type called the interlaminar cell was observed in the symbiotic tissue of the deep-sea mussel Gigantidas platifrons . These cells were found in the tissue where bacteriocytes were attached between two sheets of gill laminae.…”
Section: Resultssupporting
confidence: 56%
“…3P ). In a previous study ( 45 ), a similar cell type called the interlaminar cell was observed in the symbiotic tissue of the deep-sea mussel Gigantidas platifrons . These cells were found in the tissue where bacteriocytes were attached between two sheets of gill laminae.…”
Section: Resultssupporting
confidence: 56%